Enhance Control Mobile Compiuting Improvement in Quality Data Acquisition in Simulation - Efendi, Syahril; Aryza, Solly; Mardiansyah, Heru; Ahmadi, Fauzan Nur; Khowarizmi, Al- (Budapest International Research and Critics University, 2021)
This research is a research and development (R&D) process with software design and testing using the v-model software development life cycle (SDLC) method, consisting of stages: (1) requirements modeling, (2) architectural design, (3) component design, (4) code generation, (5) unit testing, (6) integration testing, (7) system testing, (8) acceptance testing. Unit testing method using a white-box technique with base-path test, flowgraph, independent path on